PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA BANK NAGARI CABANG LUBUK SIKAPING - Yurasti Yurasti (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2015)
THE IMPACT OF SERVICE QUALITY ON CUSTOMER SATISFACTION WITH BANK NAGARI BRANCH LUBUK SIKAPING This study aims to determine how much the influence of the dimensions of service quality to the level of satisfaction felt by customers who use the services of Bank Nagari Lubuk Sikaping Branch. The model which is used in this study is the method of observation, interviews, questionnaires, and literature study by using a likert scale and sampling method used was accidental sampling a total of 100 samples. The analytical method used is multiple linear regression method (multiple linear regression). The results showed that the dimensions of service quality consists of Tangible (X1), Empathy (X2), Responsiveness (X3), Reliability (X4), and Assurance (X5) collectively - have the same positive effect. Where the regression equation Y = 10.671 + 0.688 X1 + 0.057 X2 + 0.318 X3 + 0.996 X4 - X5 + 0.209 + e. In addition, the F-test shows that the quality of services has a significant impact on customer satisfaction with a significant level of 0.000 or 0%. While based on partial test (t), all the variables also have a significant impact on customer satisfaction for Tangible significance level is 0.001, or 0.1%; Empathy is 0,001, or 0.1%; Responsiveness 0.001 or 0.1%; Reliability 0,000 or 0%; Assurance of 0.004 or 0.4%. Keywords: Customer Satisfaction, Tangible, Empathy, Responsiveness, Reliability, and Assurance.